COLLABORATIVE GOVERNANCE DALAM PELAKSANAAN PROGRAM PENGELOLAAN SAMPAH PLASTIK BERBASIS EKONOMI SIRKULAR DI INDUSTRI PENGELOLAAN SAMPAH TERPADU ATASI SAMPAH MANDIRI (IPST ASARI) - Janah, Samrotul; Darmawan, Zikri Dwi; Ningrum, Monica Ayu; Dewi, Maya Puspita (Gapenas Publisher, 2025)
Waste is a public problem, responding to and dealing with this problem is not only the responsibility of the government, but also requires the role of various parties, including the private sector (companies). For companies, handling waste problems is related to social and environmental responsibility. This research aims to determine the Collaboration Process in the Circular Economy-Based Waste Management Program at IPST ASARI, Kotabumi Village, Cilegon City using the Collaboration model theory from Ansell and Gash (2008). Descriptive qualitative research method, with data collection techniques, namely interviews, observation, documentation and literature studies. Data analysis uses the Miles and Huberman model in Sugiyono (2013:247). Test the validity of the data using triangulation of sources and techniques, as well as member checking. The research results show that collaboration has not gone well, where several variables have not run optimally, in initial conditions there is still an imbalance in human resources and budget; in the institutional design, collaboration actor participation is still lacking, collaboration forums are held incidentally and there are no exclusive forums, facilitative leadership is still not capable of being a facilitator and mediator for collaboration actors; In the collaboration process, face-to-face meetings are held incidentally.